Comparing the history of signalling pathway research using the research publication record of representative genes. - Attrill, H. (microPublication Biology, 2023)
The development and application of genetic techniques in the fruit fly Drosophila melanogaster underlies some major advances in the understanding of metazoan development and biology. To examine whether the publication record for signalling pathway genes can indicate which factors have shaped pathway research, the publication history of selected genes is used to compare differences in research output over time. This is used to discuss how research trends may be shaped by a variety of factors such as advances in technology, ease of study and importance to human health.